A study of understanding SMEs digitalization adoption through t-o-e framework in Malaysia, Klang valley - Raymond, Disu; Yo, Ming En (2018)
Digital technology is advancing at a phenomenal pace and it’s showing no sign of slowing down. Through the various industries and markets, digital technology has helped today’s workforce work smarter. Not only are we working smarter as a global workforce, but we’re communicating more efficiently and we’re becoming more productive in our workflow. Technology has become an influential factor in our everyday lives. The main purpose of this study is to identify the relationship between TECHNOLOGY, ORGANIZATION, ENVIRONMENT and SMEs DIGITALIZATION ADOPTION in Klang Valley, Malaysia. The three variables are adopted from the T-O-E Framework, created by Tornatzky & Fleischer (1990). Judgmental sampling was utilized in this study where the researcher chooses the respondents based on the researcher’s professional judgement and knowledge. A total of 199 responses were received and analysed. The results of this study revealed that, TECHNOLOGY and ORGANIZATION are positively related towards SMEs digitalization adoption intention. Meanwhile, there is no significant relationship between ENVIRONMENT and SMEs digitalization adoption intention. In addition, the findings of this research also indicated that the digitalization adoption of SMEs is based on the knowledge, innovativeness, and skilful of personnel or management. Environment has minimal effect to the adoption of digitalization among SMEs.